STUDI PENGARUH RUSUK PENGAKU TERHADAP TEKUK LATERAL STRUKTUR BAJA DENGAN METODA ELEMEN HINGGA - Butarbutar, Sopar
This thesis to discuss regarding influence of stiffener toward lateral buckling steel structures with utilized finite element method, especially I beam with thin walled structures. The analysis base on finite element formulation, with using rectangular element. This discussion are limited only elastic condition. The programme execution result showing that is stiffner having the influence to lateral buckling, there is improve critical load beam structures. The total amount of improvement depend on loading caracteristic, beam structures and stiffener.